Dose estimates of occupational radiation exposure during radioguided surgery of Tc-99m-PSMA-labeled lymph nodes in recurrent prostate cancer - Schmidt, Daniel; Grosse, Jirka; Mayr, Roman; Burger, Maximilian; Hellwig, Dirk (Nuklearmedizin - NuclearMedicine, 2021)
Aim [99mTc]Tc-PSMA-based radioguided surgery (TPRS) represents a curative approach for localized relapse of prostate cancer. For its simplified regulatory permission, the radiation protection authorities require a 99mTc- activity below the exemption limit of 10 MBq at the time of surgery. Our aim was to determine the optimal amount of radioactivity (OAR) to comply with that limit and to estimate the maximum number of TPRS procedures per year and surgeon without triggering the full monitoring obligations.Methods In this retrospective study, a dose rate meter was calibrated using measurements on phantoms and from recently injected (1 min p. i.) patients to determine the activity in the patient from measured dose rates. The effective half-life of 99mTc-PSMA-I&S in patients was determined from repeated dose rate measurements to estimate dose parameters of relevance for radiation protection. External exposures of the surgeons were measured with personal dosimeters calibrated in Hp(10). The surgeon’s finger dose Hp(0.07) is estimated from radioactivity measured in resected lymph nodes. Potenzial incorporations were estimated for an activity of 10 MBq.Results From the first 6 subsequent patients, an effective half-life of 4.15 h was observed. Assuming an operation time 24 h p. i., the OAR was 550 MBq. Operations lasting in average 2 h in a distance of 0.25 m to the patient imply a body dose for surgeons of 4.16 µSv per procedure. Based on these estimates, the surgeon’s Hp(10) is less than 1 mSv per year with up to 241 operations per year. Hp(0.07) and potential incorporation of activity do not lead to further limitations.Summary All radiation protection regulations are met with adherence to OAR recommended here without triggering the full monitoring obligations from radiation protection regulations.
Keywords: prostate-specific membrane antigen; prostate cancer; radioguided surgery; theragnostic; radiation protection